PROACTIVE SUSTAINABLE APPROACHES BY MALAYSIAN FEEDER SERVICE COMPANIES IN THE DISRUPTIVE ERA: Article 2 - ZAINUDDIN, M.D.F.; SALLEH , N.H.M.; MHD RUSLAN, S.M. (Journal of Maritime Logistics, 2021)
Feeder services play a significant role in Malaysian shipping economy. A total of 87.5 per cent of feeder companies have established themselves in Port Klang, as their focal point of service, while the remaining 12.5 per cent have chosen neighbouring Singapore Port as their base. Recently, the industry players have faced many challenges, such as hyper-competition, price wars, the COVID-19 pandemic, and threats of bankruptcy, which leads to the situation known as the disruptive era. While plenty of studies have discussed the issues of feeder services by focusing on the “hub and spoke” design, route design and environmental context, there is lack of research on proactive sustainable approach in the case of Malaysia feeder services. As a result, this paper reviews the impact of the United States-China trade war, COVID-19 pandemic and hyper-competition among feeder service companies in Malaysia. An extensive literature review and online interviews are conducted with feeder service operators, government agencies and port authorities, and the data analysed using Thematic Analysis. The results show that offering competitive freight rates, reliable services and alliance between feeder operators are important in business sustainability. Meanwhile, unstable oil prices, high chartering costs and less creativity in problem-solving are factors that reduce business sustainability. This paper hopes to assist feeder service operators, researchers and government agencies in understanding and planning sustainable strategies for the industry in the disruptive era.